Early-stage researcher mobility: Gender barriers and opportunities in capacity building - Reyes, Byron; Camilo, Karen; Villarino, Eliza; Rietveld, Anne; Keramati, Chista; Monjol, Joanne; Spillane, Charles; Murray, Una; Aganze Chihababo, Christian (2024)
A climate-related capacity-building program should not only enhance developing country parties' capacity and ability to implement adaptation and mitigation actions (Article 11.1 of the Paris Agreement) but also, ensure socially inclusive training that fosters equality of both opportunity and outcome, particularly for cohorts who are poor or otherwise marginalized. Framed on this, CLIFF-GRADS is a training program that builds the capacity of early-career scientists from low- and middle-income countries to conduct applied research in agriculture GHG emission quantification and mitigation; however, current assessments of the CLIFF-GRADS program show that women are not only under-represented but also not applying to the program as frequently as men. Our research seeks for understanding the constraints candidates face before, during, and after they complete their fellowship and identify ways to make this program more inclusive.